Large Binocular Telescope observations of PSR J2043+2740. Issue 2 (27th September 2017) - Testa, V.; Mignani, R. P.; Rea, N.; Marelli, M.; Salvetti, D.; Breeveld, A. A.; Cusano, F.; Carini, R.
Abstract: We present the results of deep optical imaging of the radio/γ-ray pulsar PSR J2043+2740, obtained with the Large Binocular Telescope (LBT). With a characteristic age of 1.2 Myr, PSR J2043+2740 is one of the oldest (non-recycled) pulsars detected in γ-rays, although with still a quite high rotational energy reservoir (E_rot = 5.6 × 10^34 erg s −1 ). The presumably close distance (a few hundred pc), suggested by the hydrogen column density ( N H ≲ 3.6 × 10 20 cm −2 ), would make it a viable target for deep optical observations, never attempted until now. We observed the pulsar with the Large Binocular Camera of the LBT. The only object ( V = 25.44 ± 0.05) detected within ∼3 arcsec from the pulsar radio coordinates is unrelated to it. PSR J2043+2740 is, thus, undetected down to V ∼ 26.6 (3σ), the deepest limit on its optical emission. We discuss the implications of this result on the pulsar emission properties.